PENGEMBANGAN BUKU PANDUAN ALAT MUSIK RECORDER PADA PEMBELAJARAN SENI MUSIK KELAS V SDN 01 PERMANU - Andika Gutama; Cicilia Ika Rahayu Nita; Ruth Natalia Damayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
There are three branches of arts education at SDN 01 Permanu, namely visual arts, music, and dance. Although all three are taught, the school tends to focus more on visual arts education because it is considered easier to implement and supported by the availability of adequate tools and materials. Meanwhile, music education still faces challenges, particularly with the recorder instrument material, as students struggle with properly placing their fingers on the recorder holes, blowing with the correct technique, and reading musical notation. This study aims to determine the process, feasibility, practicality, and effectiveness of the recorder instrument guidebook. This development research uses the Research and Development (R&D) method with the ADDIE model: analysis, design, development, implementation, and evaluation. The subjects in this study included media experts, subject matter experts, and language experts for feasibility testing, as well as teachers and students for practicality testing through limited field testing involving 3 students and extensive field testing involving 5 students. The feasibility test results showed a 95.45% approval rate by media experts, 95% by subject matter experts, and 90% by language experts, categorizing the guidebook as “Highly Feasible.” The practicality test by teachers yielded a percentage of 79.16%, which can be categorized as “Very Practical.” The practicality percentage by students in the limited field test was 99.16%, and by students in the extensive field test was 79%, both falling under the “Very Practical” category. The effectiveness test on the skill aspect using a questionnaire yielded a percentage of 83.43%, categorized as “Very Effective.” Based on the research results, it can be concluded that the music recorder playing guidebook is categorized as suitable, practical, and effective for use in music education at elementary schools.